Prognostic factors of survival in patients with non-infectious mixed cryoglobulinaemia vasculitis: data from 242 cases included in the CryoVas survey. Issue 3 (14th May 2012) - Terrier, Benjamin; Carrat, Fabrice; Krastinova, Evguenia; Marie, Isabelle; Launay, David; Lacraz, Adeline; Belenotti, Pauline; de Saint Martin, Luc; Quemeneur, Thomas; Huart, Antoine; Bonnet, Fabrice; Le Guenno, Guillaume; et al.
Abstract : Background: Data on the prognosis of non-infectious mixed cryoglobulinaemia vasculitis (CryoVas) in the era of hepatitis C virus screening are lacking. Methods: The French multicentre and retrospective CryoVas survey included 242 patients with non-infectious mixed CryoVas. Causes of death and prognostic factors of survival were assessed and a prognostic score was determined to predict survival at 5 years. Results: After a median follow-up of 35 months, 42 patients (17%) died. Causes of death were mainly serious infections (50%) and vasculitis flare (19%). One-, 2-, 5- and 10-year overall survival rates were 91%, 89%, 79% and 65%, respectively. A prognostic score, the CryoVas score (CVS), for the prediction of survival at 5 years was devised. Pulmonary and gastrointestinal involvement, glomerular filtration rate <60 ml/min and age >65 years were independently associated with death. At 5 years the death rates were 2.6%, 13.1%, 29.6% and 38.5% for a CVS of 0, 1, 2 and ≥3, respectively. At 1 year the death rates were 0%, 3.2%, 18.5% and 30.8% for a CVS of 0, 1, 2 and ≥3, respectively. The CVS was strongly correlated with the Five Factor Score (FFS) 2009, another prognostic score validated in primary necrotising vasculitis (r=0.82; p<0.0001). The area under the curve for the CVS was 0.74 compared with 0.67 for the FFS, indicating a better performance of the CVS (p=0.052). Conclusions: In patients with non-infectious mixed CryoVas, the main prognostic factors are age >65 years, pulmonary and gastrointestinal involvement and renal failure. A score including these variables is significantly associated with the prognosis.